A comparative expression analysis of gene transcripts in brain tissue of non-transgenic and GH-transgenic zebrafish (Danio rerio) using a DDRT-PCR approach - Alves-Costa,Fernanda A. (2012)
The presence of higher level of exogenous growth hormone (GH) in transgenic animals could lead to several physiological alterations. A GH transgenic zebrafish (Danio rerio) line was compared to nontransgenic (NT) samples of the species through a DDRT-PCR approach, with the goal of identifying candidate differentially expressed transcripts in brain tissues that could be involved in GH overexpression. Densitometric analyses of two selected amplification products, p300 and ADCY2, pointed to a significant lower gene expression in the transgenic zebrafish (104.02 ± 57.71; 224.10 ± 91.73) when compared to NT samples (249.75 ± 30.08; 342.95 ± 65.19). The present data indicate that p300 and ADCY2 are involved in a regulation system for GH when high circulating levels of this hormone are found in zebrafishes.